2016
DOI: 10.1001/jamaoncol.2016.0639
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for the Clinical Use of PD-1/PD-L1 Inhibitors in Non–Small-Cell Lung Cancer

Abstract: The refinement of existing biomarkers and identification of novel predictive biomarkers will be key to ensuring the effective and safe use of these agents. Since most patients still do not benefit from these agents, it is critical to continue to work to define the select patient population who will derive durable benefit from PD-1/PD-L1 inhibition and identify markers that could have predictive value for combination therapies that could expand the population who benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
188
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(190 citation statements)
references
References 32 publications
(35 reference statements)
1
188
0
1
Order By: Relevance
“…Most studies evaluated PD-L1 expression as the percentage of tumour cells showing cell-surface and/or membranous PD-L1 staining in a section containing at least 100 evaluable tumour cells; however, different assays and antibodies are currently used to detect PD-L1 staining, without standardization 48,49 . Moreover, variable cut-off values and different scoring methods have been used to define PD-L1 positivity on IHC (TABLE 2).…”
Section: Biomarkers Of Immunotherapy Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Most studies evaluated PD-L1 expression as the percentage of tumour cells showing cell-surface and/or membranous PD-L1 staining in a section containing at least 100 evaluable tumour cells; however, different assays and antibodies are currently used to detect PD-L1 staining, without standardization 48,49 . Moreover, variable cut-off values and different scoring methods have been used to define PD-L1 positivity on IHC (TABLE 2).…”
Section: Biomarkers Of Immunotherapy Responsementioning
confidence: 99%
“…For all assays, greater variability in PD-L1 staining was found in immune cells than in tumour cells 52 . The study indicated that interchanging assay methods and cutoff values for PD-L1 positivity can lead to inconsistent classifications of PD-L1 status in some patients 52 , highlighting the limitations of the current IHC approach to assessing PD-L1 expression in terms of reproducibility, as well as in sampling variability 49 .…”
Section: Biomarkers Of Immunotherapy Responsementioning
confidence: 99%
“…Programmed death-ligand 1 expression is heterogeneous and can be induced in response to a number of stimuli. Although tumour PD-L1 expression levels generally correlate to responses with immune therapy agents, some PD-L1 negative tumours still respond to these agents 59 . As well, each of the five therapeutic monoclonal antibodies has a different ihc-based companion or complementary biomarker test to measure the PD-L1 protein expression.…”
Section: Recommendationmentioning
confidence: 99%
“…Despite the development of FDA-approved assays for PD-L1 testing, some clinics use laboratorydeveloped tests, which can be less costly but can also increase the amount of testing variability [86]. Variability in PD-L1 testing can arise because of the type (tumor cells, immune cells, or a combination) and percentage cutoffs used for positivity, archival versus fresh tissue, primary versus metastatic biopsies, diversity of antibodies utilized, and tumor heterogeneity [86,87]. Several comparative studies across different PD-L1 assays have been conducted, including collaborative studies between industry and academic institutions [88][89][90][91].…”
Section: Immunotherapeutics and Patient Selectionmentioning
confidence: 99%